Perceived stress levels, associated factors and non-pharmacological stress management strategies amongst pharmacists in the Volta Region of Ghana - Gabriel K.N. Essilfie-Essel; Ebenezer Wiafe; Afia F.A. Marfo; John K.A. Korbuvi; Varsha Bangalee (Scientific African)
Ghanaian studies on high-stress levels in the healthcare system's workforce have focused on healthcare workers in general. The available pharmacy-specific study utilized pharmacy students. Hence, an investigation into the stress levels of Ghanaian pharmacists and the potential detrimental effect, including dispensing errors, on patients’ safety is worth studying. This study investigated the factors associated with the stress levels of pharmacists working in the Volta Region of Ghana and examined their non-pharmacological stress management strategies. A cross-sectional study, employing web-based questionnaires, was conducted amongst registered pharmacists working in the Region. The data sets were analysed in SPSS version 25. Using binary logistic regression, associations were measured with odds ratios. Statistical tests were set at 95 % confidence intervals and p-values set at 5 % significance. The study had a response rate of 53.19 %. The prevalence of stress was 68 % with a mean Perceived Stress Scale (PSS) score of 17.40. Males had 2.11 higher mean PSS scores than females. The PSS between married and single pharmacists were similar. Pharmacists with small family sizes had higher PSS scores than those with larger (>7) family sizes. There were no statistically significant associations between gender, years of practice, family size, religion, marital status and stress. Walking, sitting meditation and walking meditation were the three top non-pharmacologic stress coping mechanisms. The prevalence of stress recorded was 68 %. Male pharmacists perceived higher stress than females. Walking was the most popular non-pharmacologic approach to stress.